Analisis Kesalahan Struktur Kalimat pada Tes Keterampilan Menulis dalam Diklat HSK 3 (汉语水平考试) Guru Bahasa Mandarin SMA/SMK di PPPPTK Boe Malang - Lestari Puspitaningsih (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2018)
This study is aimed to investigate the types of sentence errors made by Mandarin High School Teachers who joint HSK 3 teacher training. In linguistics, according to J. Richard et al., (2002), an error is the use of a word, speech act or grammatical items in such a way it seems imperfect and significant of an incomplete learning. The study was conducted using a comparative taxonomy which was to analyze the results of training participants' writing skills tests contained in HSK 3 caused by interlingual errors or called also interference errors, where errors originating caused the influence of the first language (B1) on the second language languages (B2) and intralingual errors caused lack of understanding of the second language. Analysis results show that there are five sentences where as many as 85% of respondents make mistakes due to confusion with the structure in Indonesian. The occurrence of error analysis is don’t only to indicate the cause, but also as a study for applying the appropriate method in implementing learning Mandarin.